Guiding principles for the implementation of a standardized psychological autopsy to understand and prevent suicide: a stakeholder analysis - Balt, Elias; Heesen, Karlijn; Popma, Arne; Gilissen, Renske; Mérelle, Saskia; Creemers, Daan (Frontiers in Psychiatry, 2023)
Abstract Background: Around 700.000 people die by suicide each year. While the global number of suicides declined over the last decade, the rates remained unchanged in the Netherlands. With this study, we aimed to provide guiding principles for the implementation of a national standardized psychological autopsy to better understand and prevent suicide, by exploring stakeholder perceptions and needs, and barriers to implementation. Methods: We interviewed 47 representative stakeholders from various fields (e.g., mental healthcare professionals, policy advisors, researchers). A semi structured interview design was used, based on the RE-AIM and Consolidated Framework for Implementation Research (CFIR) theoretical frameworks. Results: Themes relating to stakeholder perceptions and needs for a standardized psychological autopsy included valorization, accountability, integrability and the needs of the bereaved. Stakeholders believed that participation in a psychological autopsy can help bereaved in their process of grief but noted that evidence to frame the psychological autopsy as postvention is insufficient. The primary focal point should accordingly be to better understand and prevent suicide. Several key limitations of the proposed psychological autopsy approach were detailed, both methodological and implementational. Conclusions: The stakeholder analysis delineates guiding principles for implementation. Stakeholders believe that a standardized psychological autopsy has merit, provided that key considerations, including valorization and accountability, are integrated in its design. Routine evaluation should be ensured. The findings may guide policy makers and researchers in their endeavours to support a learning, community-based approach for suicide prevention based on a standardized psychological autopsy.